ASSESSMENT OF RISK FACTORS OF DIABETES MELLITUS IN THE URBAN FIELD PRACTICE AREA OF A TERTIARY CARE HOSPITAL OF SOUTHERN ODISHA: A CROSS-SECTIONAL STUDY - SHRABANI, PALAI; NIVEDITA, KARMEE; SANGEETA, DAS; M DURGA, SATAPATHY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Diabetes is a chronic state of hyperglycemia which results in complications involving organs such as eyes, kidneys, nerves, heart, and blood vessels. Identifying the risk factors at an early stage can help in reducing the complications and co-morbidities of the disease. Hence, the study is carried out to assess the socio-demographic profile and associated risk factors of adult patients with diabetes mellitus. Methods: It was a cross-sectional study carried out in the urban field practice area of M.K.C.G Medical College for a period of 2 years. Multistage simple random sampling was used to select 160 known diabetic cases. Data were collected using a pre-tested questionnaire and anthropometric measurements were taken. Data were analyzed in SPSS version 17 and appropriate statistical tests were used. Results: The mean age of study participants was 53.94. About 41.88% and 21.25% were current tobacco and alcohol users, respectively. Inadequate fruit and vegetable consumption, mixed type diet, obesity in the form of increased body mass index, and waist hip ratio and sedentary life style were found to be the predisposing factors of the disease. Conclusion: Early identification of at risk individuals and appropriate intervention to increase physical activity, bring about changes in dietary habits, maintenance of correct body weight could help to prevent or delay the onset of the disease to a great extent.